ELEMEN KOREOGRAFI TARI PENYAMBUTAN PRASNAYA PRAMI - Ni Komang Sri Wahyuni; Ni Made Liza Anggara Dewi; Ni Nyoman Ayu Kunti Aryani (Jurnal Seni Makalangan, 2025)
Karya Tari Prasnaya Prami merupakan tari penyambutan yang menggabungkan nuansa gerak tari Jawa dan Bali sebagai inovasi dalam pengembangan tari penyambutan di Bali. Perpaduan ini merefleksikan keharmonisan budaya serta memvisualisasikan simbol keramahan yang sejalan dengan nilai Pawongan dalam Tri Hita Karana. Secara etimologis, prasnaya berarti penghormatan dan prami merujuk pada sosok perempuan anggun dan penuh kasih, yang menjadi dasar artistik dalam membangun karakter tarian. Karya ini merupakan bagian dari Program P2SD Berdampak ISI Bali 2025 dan telah didiseminasikan pada Bali Nata Bhuwana Nasional 2025 di Yogyakarta. Penulisan ini menggunakan konsep pemikiran Y. Sumandiyo Hadi mengenai elemen koreografi dengan pendekatan kualitatif melalui observasi, wawancara, dan dokumentasi. Hasilnya berupa pencatatan struktur koreografi yang mencakup (1) Jumlah penari, jenis kelamin, dan postur tubuh, (2) Ruang tari, (3) Iringan/musik tari, (4) Gerak tari, (5) Judul tari, (6) Tema tari, (7) Tipe/jenis/sifat tari, (8) Mode/cara penyajian, (9) Rias dan kostum tari, (10) Tata cahaya, dan (11) Properti tari. ABSTRACT CHOREOGRAPHIC ELEMENTS OF THE PRASNAYA PRAMI WELCOMING DANCE, DECEMBER 2025. Prasnaya Prami is a welcoming dance that integrates movement nuances from Javanese and Balinese dance traditions as an innovative contribution to the development of welcoming dances in Bali. This fusion reflects intercultural harmony and embodies the symbolism of hospitality aligned with the Pawongan values in the Tri Hita Karana philosophy. Etymologically, prasnaya means “honor,” while prami refers to a graceful and gentle woman, forming the artistic foundation of the dance’s character. Created as part of the 2025 P2SD Berdampak Program of ISI Bali, the work was presented at the 2025 Bali Nata Bhuwana National event in Yogyakarta. This writing employs Y. Sumandiyo Hadi’s conceptual framework on choreographic elements using a qualitative approach through observation, interviews, and documentation. The findings present a detailed mapping of the choreography, including (1) number, gender, and posture of dancers, (2) dance space, (3) musical accompaniment, (4) movement vocabulary, (5) title, (6) theme, (7) type/character of dance, (8) mode of presentation, (9) makeup and costume, (10) lighting design, and (11) properties used. Keywords: Choreographic Elements; Prasnaya Prami.